Smart helicopter rotors : optimization and piezoelectric vibration control /: optimization and piezoelectric vibration control. ([2015]) - Ganguli, Ranjan; Thakkar, Dipali; Viswamurthy, Sathyamangalam Ramanarayanan
No abstract available